Developing people capabilities for the promotion of sustainability in facility management practices - Sarpin, Norliana (2015)
Sustainability is becoming an integral part of the life-cycle development of built facilities. It is increasingly highlighted during the post construction phase, as facility management personnel can have major influence to the sustainability agenda through operational and strategic management functions. Sustainable practices in facility management can bring substantial benefits such as reducing energy consumption and waste, while increasing productivity, financial return and corporate standing in the community. Despite the potential, facility managers have yet to embrace sustainability ideas holistically and implement them in their operation. The lack of capabilities and skills coupled with knowledge gaps are among the barriers. In the developmental context, capabilities are vital to foster the competency of an organisation. Facility managers need to be empowered with the necessary knowledge, capabilities and skills to support sustainability. This research investigates the potential people capabilities factors that can assist in the implementation of sustainability agenda in facility management practices. Through questionnaire survey, twenty three critical people capability factors were identified and encapsulated into a conceptual framework. The critical factors were separated into four categories of strategic capabilities, anticipatory capabilities, interpersonal capabilities and system thinking capabilities. Pair-wise comparison and Interpretive Structural Modelling techniques were then used to further explore the interrelationship and influence of each critical factor. An interpretive structural model for people capability was developed to identify the priority of critical factors and provide a hierarchical structure to guide facility managers for appropriate actions. The research concludes with three case-studies of professional facility management practices to finalise the developed people capabilities framework and interpretive structural model. Through the identification and integration of different perceptions and priority needs of the stakeholders, a set of guidelines for action and potential effects of each people capability factor were brought forward for the industry to promote sustainability endeavour in facility management practices.